Implementation of the Rapid Application Development Approach for the Academic Information System at Muzakkir Islamic Primary School Prabumulih - Ardi Ardiansyah; Andi Christian; Nur Aini Hutagalung (Yayasan Kita Menulis, 2026)
This study stems from the limited application of information technology, which continues to influence various aspects of human life—particularly in the fields of employment, business, and, more specifically, at Muzakkir Islamic Elementary School in Prabumulih, where data management is still handled through conventional methods. Data for this research was collected using a descriptive method with a qualitative approach, employing observation, interviews, and literature review. The design of the academic information system applied the Rapid Application Development (RAD) methodology to assist developers in analyzing and designing the system based on actual needs. The Unified Modeling Language (UML) served as a tool for designing the school’s academic information system, supporting the developers during the process. The developed system was implemented using the Hypertext Preprocessor (PHP) programming language and a MySQL database.